Analisis Faktor Dengan Kejadian Tinea Corporis (KURAP) Terhadap Kebersihan Diri Di Desa Nelayan Wilayah Kerja Puskesmas Padongko Kabupaten Barru - Rosdiana Rosdiana; Iskandar Zulkarnaen; Alief Ihram Fatany; Ima Mustika Tri Lestari; Haedir Haedir; Rahmat Pannyiwi (Journal on Education, 2025)
Personal hygiene is personal hygiene that is carried out to maintain health, both physically and psychologically. According to Entjang, the definition of personal hygiene or individual hygiene (personal health efforts) is an effort by a person to maintain and improve their own health. The purpose of this study was to analyze the effect of personal hygiene on the incidence of tinea corporis (ringworm) in fishing communities. This research method is an analytical survey study using a cross-sectional research design. The population was 150 people and 50 people were taken randomly, data analysis using the chi-square test and multiple logistic regression. The results of this study are There is a significant relationship between Personal Hygiene (skin hygiene), with the incidence of tinea corporis (ringworm). The conclusion is that the community should maintain personal hygiene by maintaining skin hygiene, to reduce the risk of tinea corvoris (ringworm) disease.